1995
DOI: 10.1007/s002800050351
|View full text |Cite
|
Sign up to set email alerts
|

Gender affects doxorubicin pharmacokinetics in patients with normal liver biochemistry

Abstract: We studied the variability in doxorubicin pharmacokinetics in 27 patients, all of whom had normal liver biochemistry tests. Blood samples were collected after the first cycle of single-agent doxorubicin given as an i.v. bolus and plasma levels were measured by high-performance liquid chromatography (HPLC). The relationship of doxorubicin clearance (dose/AUC) with biochemical tests (AST, bilirubin, alkaline phosphatase, albumin, creatinine) and physical characteristics (age, gender, height, weight, tumour type)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…Although pharmacodynamic studies have reported sex differences in toxicity for some anti‐cancer drugs (e.g., doxorubicin and 5‐fluorouracil), this study compares toxicities for females and males treated for ALL in the context of two large, phase III cooperative group clinical trials. The toxicities reflect synergistic and additive effects of multiple therapies, including both cancer‐directed treatments and supportive care treatments (e.g., antibiotics).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pharmacodynamic studies have reported sex differences in toxicity for some anti‐cancer drugs (e.g., doxorubicin and 5‐fluorouracil), this study compares toxicities for females and males treated for ALL in the context of two large, phase III cooperative group clinical trials. The toxicities reflect synergistic and additive effects of multiple therapies, including both cancer‐directed treatments and supportive care treatments (e.g., antibiotics).…”
Section: Discussionmentioning
confidence: 99%
“…Liver clearance for methotrexate and doxorubicin, both drugs used in the treatment of childhood ALL, is lower for adult females than adult males, resulting in higher drug levels and toxicities for females . Dobbs et al found that, among adult patients with normal liver biochemistry, sex was the only factor predicting doxorubicin clearance after adjusting for BSA . These findings are significant as rapid drug clearance (e.g., doxorubicin and methotrexate) is associated with reduced cure rates …”
Section: Discussionmentioning
confidence: 99%
“…In adults, a lower plasma clearance of doxorubicin has been observed in females as compared to males [25]. It has also been reported that nausea associated with anthracycline-containing regimens is more severe in girls than in boys [26] and that girls run a higher risk of abnormalities in cardiac function [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al performed a sexbased retrospective analysis of four SCLC trials conducted by the Clinical Trials Group of the National Cancer Institute of Canada between 1987 and 1999, including 648 male and 358 female patients that received a chemotherapy consisting of cyclophosphamide-doxorubicin-vincristine (CAV) followed by etoposide-cisplatin (EP) treatment [11]. For the SCLC treatment, it was suggested that the differences in toxicity might be related to reduced hepatic clearance of etoposide or doxorubicin in women [11], which was reported previously [32,33]. The differences identified were highly significant and remained significant after the adjustments on potentially confounding covariates, such as age, performance status, and pretreatment lactate dehydrogenase (LDH) values [11].…”
Section: Sex-drug Interaction: Sex Difference In Toxicity and Pharmacmentioning
confidence: 90%
“…Four major factors may contribute to the pharmacokinetic variability in sex differences -absorption, distribution, metabolism and excretion [16]. Existing evidence indicates that the clearance values of many chemotherapeutic drugs, e.g., 5-FU [35] and doxorubicin [32], are lower in women compared with men. The fact that females weigh less and have a higher percent body fat than males may affect drug distribution and potentially increase toxicity, but this alone can not adequately account for observed differences in toxicity [7].…”
Section: Sex-drug Interaction: Sex Difference In Toxicity and Pharmacmentioning
confidence: 99%